Simulations of EIA screening across jurisdictions: exposing the case for harmonic criteria?. Issue 3 (3rd July 2017) - Rocha, Caroline Priscila Fan; Fonseca, Alberto
Abstract: Screening is one of the most critical stages in environmental impact assessment (EIA). However, there is no consensus about best approaches to screen development proposals, particularly in large territories with multiple jurisdictions. This study explored the challenges of harmonizing EIA screening criteria across jurisdictions, using Brazilian states as the empirical context. It set out to answer the following question: what would be the screening decisions of approved development projects if they had been licensed in different states? This study selected four cases of projects that had obtained environmental licenses in the state of Minas Gerais, and, based on their data, simulated license applications in other three states in south-eastern Brazil. Interviews helped to determine likely screening decisions. Screening approaches, while similar, varied significantly in terms of choices of threshold criteria across the four states. With the exception of one project type, the projects would face very different EIA requirements in the other jurisdictions. Such differences seem to stem more from political choices than from geographical idiosyncrasies. Implications for policy-making regarding harmonization are discussed.